על האנוכתב - בנימיני, יצחק (מכאן, 2016)
The concept of the ‘subjectext’ developed in this article is put forward, first, in an attempt to account for the nature of ‘divine address’ - examples of which include God’s addressing of Abraham, “Get thee out of thy country” (Lech lecha, Genesis 12:1) and God’s reply to Moses, “I am that I am” (Ehyeh asher ehyeh, Exodus 3:14). The theoretical model proposed here regards the divine address as deriving from a source of authority allegedly exterior to the subject, a source who addresses its message to a particular addressee, and who interpellates that addressee into becoming a subject of faith, that is, one who believes in, and works towards, an external ideological cause. The second related thesis of the article involves yet another register of revelation and divine address, namely that which takes place between the biblical text and its reader. It demonstrates how the expression “Lech lecha” simultaneously addresses Abraham while performing an interpellative act of faith on the reader, who in turn becomes what the article suggests calling a ‘subjectext’. The article then poses the question of whether the divine text and the divine ‘other’ re-constitute the reader within the field of ‘otherness’, or whether they are but a mirror-image of the secret desire of the reader/believer. It argues that a close reading of these verses suggests that the passage to Canaan was a familial mission - an interrupted one - irrespective of God’s intervention. Divinity (the God-‘other’) seized upon this situation of temporary stasis in order to encourage the subject (Abraham) to fulfill his destiny. In this sense, the other is not an entirely external voice revealing itself ex nihilo, but represents for Abraham, and perhaps also for the reader, the incarnation of a deep personal desire.